2018
DOI: 10.3390/soc8010019
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Clothing as a Barrier to Workplace Participation Faced by People Living with Disabilities

Abstract: In response to research which argues that people living with a disability (PLWD) face societal barriers including workplace participation, this study explored how the barriers to social participation, specifically workplace participation, faced by PLWD are exacerbated by the lack of appropriate clothing and the role that stigma, self-efficacy, and clothing have in workplace participation. Finding appropriate clothing is a significant barrier to social participation for many PLWD. The social model of disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…One study showed the vicious circle where a job was necessary for improving the self-esteem of people with disabilities, but a job had not been within reach due to their low self-esteem [ 106 ]. Self-stigma undermined the motivation of people with disabilities to aspire, secure, or maintain employment [ 15 , 92 , 96 ] and negatively affected their self-efficacy [ 107 ]. If people with disabilities were not motivated to undertake action to maintain or find employment due to self-stigma, it was challenging to find or maintain a job [ 24 , 39 , 108 , 109 ], e.g., due to avoidance of the prospect of promotion [ 104 ], less career achievement or advancement [ 69 ], earning less [ 110 ], not returning to work [ 106 ], dropping out, or changing career-goals [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed the vicious circle where a job was necessary for improving the self-esteem of people with disabilities, but a job had not been within reach due to their low self-esteem [ 106 ]. Self-stigma undermined the motivation of people with disabilities to aspire, secure, or maintain employment [ 15 , 92 , 96 ] and negatively affected their self-efficacy [ 107 ]. If people with disabilities were not motivated to undertake action to maintain or find employment due to self-stigma, it was challenging to find or maintain a job [ 24 , 39 , 108 , 109 ], e.g., due to avoidance of the prospect of promotion [ 104 ], less career achievement or advancement [ 69 ], earning less [ 110 ], not returning to work [ 106 ], dropping out, or changing career-goals [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…Self-stigma undermined the motivation of people with disabilities to aspire, secure, or maintain employment [ 15 , 92 , 96 ] and negatively affected their self-efficacy [ 107 ]. If people with disabilities were not motivated to undertake action to maintain or find employment due to self-stigma, it was challenging to find or maintain a job [ 24 , 39 , 108 , 109 ], e.g., due to avoidance of the prospect of promotion [ 104 ], less career achievement or advancement [ 69 ], earning less [ 110 ], not returning to work [ 106 ], dropping out, or changing career-goals [ 107 ]. Self-stigma did not only affect sustainable employment but it could also affect well-being at work because self-stigma could lead to lower help-seeking intentions [ 15 , 66 , 111 113 ] although one study did not confirm this [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…Second, the descriptions and products illustrated in Table 3 demonstrate how current industry practices and descriptors could stigmatize potential users and consumers. Past researchers have suggested that PLWD feel further stigmatized when forced to shop for apparel that is labeled as adaptive or for people with disabilities (Freeman et al, 1985; Kabel et al, 2016; McBee-Black & Ha-Brookshire, 2018). This stigmatization may result in consumers (PLWD) choosing not to shop brands using this terminology and to seek out product not marketed directly to people with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, with this study, the authors took a two-step approach: The first step was to conduct a literature review on four terms—adaptive apparel, functional apparel, universal design, and inclusive design—given that they are thought to be the most commonly used terms to describe apparel targeted to PLWD (McBee-Black & Ha-Brookshire, 2018). The second step was to survey how these four terms were used in the marketplace and to compare their usage in the marketplace to that in the literature.…”
mentioning
confidence: 99%
“…El modelo social, sin embargo, se centra en la restricción social que se impone a la discapacidad corporal, en otras palabras, no es la discapacidad lo que impide que una persona participe plenamente en la sociedad, sino que es la sociedad la que crea barreras para la participación, un claro ejemplo es la dificultad de acceder a vestimenta adecuada para ciertos eventos, la persona puede participar de dichos eventos, pero no se siente cómoda por no poder acceder a vestimenta adecuada que cubra sus necesidades (4). Social 2018;2(3):145-147. -146-Algunos autores enfatizan el hecho de que la vestimenta y la apariencia son factores importantes en la forma en que las personas sin discapacidades se comprometían con ellas, y que las discapacidades visibles aumentaban las barreras de actitud más negativas (4). Así que se vuelve al concepto anterior, el problema en sí no es la discapacidad sino las barreras que puedan ponerse para que dichas personas puedan acceder también a ropa y calzados adecuados para ellos y al mismo tiempo que cumplan los estándares estéticos de los mismos.…”
Section: Estimado Editorunclassified